PREVALENCE AND FACTORS ASSOCIATED WITH FRAILTY USING THE CLINICAL FRAILTY SCALE AMONG COMMUNITY-DWELLING OLDER ADULTS IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2026)
Background: Frailty is a prevalent geriatric syndrome characterized by increased vulnerability and an elevated risk of poor health consequences, including decline in functional capacity, falls, hospitalization, and mortality. However, little is known about the conditions associated with frailty in the elderly, which remain understudied and poorly known in Vietnam, and early community-based detection is critical for managing the complex medical and psychosocial needs of the elderly.Objective: This study aimed to explore the prevalence of frailty and its associated factors among community-dwelling older adults in Ho Chi Minh City.Method: In this cross-sectional study, a total of 317 older adults participated. Frailty was evaluated by utilising the CFS scale as a screening tool. This study was started in May 2025 and completed by November 2025.Results: The overall prevalence of frailty was found to be 14.8%, using the CFS-VN version. Multimorbidity was present in 53.0% of participants, polypharmacy in 24.9%, and IADL disability in 13.9%. In the multivariate logistic regression model, multimorbidity (aOR = 3.13, 95% CI: 1.32-7.69), polypharmacy (aOR = 2.94, 95% CI: 1.39-6.25), and IADL disability (aOR = 2.70, 95% CI: 1.19-6.67) were independently associated with a higher likelihood of frailty. Older adults aged ≥ 80 years showed an elevated but non-significant increase in frailty risk (aOR = 2.19, 95% CI: 0.83-5.79). Gender, ethnicity, BMI category, marital status, and history of falls were not significantly associated with frailty after adjustment (p > 0.05).Conclusion: In summary, multimorbidity, polypharmacy, and IADL impairment were the strongest independent correlates of frailty in this study. The CFS-VN proved to be a practical tool for initial frailty screening in community settings, particularly in urban areas of Vietnam.